Comparing Trajectory of Surgical Aortic Valve Replacement in the Early vs. Late Transcatheter Aortic Valve Replacement Era - Elbaz-Greener, Gabby; Rozen, Guy; Kusniec, Fabio; Marai, Ibrahim; Carasso, Shemy; Ko, Dennis T.; Wijeysundera, Harindra C.; Alcalai, Ronny; Planer, David; Amir, Offer (Frontiers in Cardiovascular Medicine, 2021)
Background: Traditionally, the only effective treatment for aortic stenosis was surgical aortic valve replacement (SAVR). Transcatheter aortic valve replacement (TAVR) was approved in the U.S. in late 2011 and provided a critical alternative therapy. Our aims were to investigate the trends in the utilization of SAVR in the early versus late TAVR era, and to assess SAVR and TAVR outcomes. Methods: Using the 2011-2017 National Inpatient Sample (NIS) database, we identified hospitalizations for patients with a most responsible diagnosis of aortic stenosis during which an aortic valve replacement (AVR) was performed, either SAVR or TAVR. Patients’ sociodemographic and clinical characteristics, procedure complications, length of stay and mortality were analyzed. Multivariable analyses were performed to identify predictors of in-hospital mortality. Piecewise regression analyses were performed to assess temporal trends in SAVR and TAVR utilization. Results: A total of 542,734 AVR procedures were analyzed. The utilization of SAVR was steady until 2014 with significant downward trend in the following years 2015-2017 (P=0.026). In contrast, a steady upward trend was observed in the TAVR procedure with a significant increase during the years 2015-2017 (P=0.006). Higher in-hospital mortality was observed in SAVR patients. The mortality rate declined from 2011 to 2017 in significantly higher proportion in the TAVR compared to the SAVR group. Conclusion: Utilization of SAVR showed downward trend during the late TAVR era (2015-2017) while TAVR utilization demonstrated a steady upward trend during the years 2011-2017. Higher in-hospital mortality was recorded in patients who underwent SAVR.